Draft Annual Plan 2011-12 Government of Goa - Planning Commission (Planning Commission, 2011)
The economy of the State has been growing above 11 per cent for the past few years. During 2008-09, however, the Gross State Domestic Product (GSDP) at constant prices has grown at the rate of 7.2 per cent with 1999-2000 as the base year as against 14.13 per cent in 2007-08. The sectoral growth rate for primary, secondary and Tertiary sectors for 2008-09 have been (-) 1.57, 9.50 and 7.60 per cent respectively as compared to (-) 0.23, 9.42 and 21.80 per cent respectively in 2007-08. The global economic crisis has adversely affected the State’s economy causing disruption to the growth momentum achieved during the last few years.
Government of Goa, Directorate of Planning, Statistics and Evaluation